(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Photodynamic therapy (PDT) consists of the association of a photosensitizing agent with a light source in order to cause cellular necrosis. Methylene blue, toluidine blue and malachite green are photosensitizers derived from dyes that are widely accepted in medicine, as they have low toxicity and are low cost. PDT is an alternative treatment for cancer, with significant advantages over procedures such as surgery/chemotherapy. Our laboratory has studied the Fricke solution doped with photosensitizers in an approach to obtain a quality control for PDT. The Fricke solution was prepared with ammoniacal ferrous sulfate, sodium chloride and sulfuric acid in water. The solutions modified with photosensitizers were prepared by adding 0.1 g/100 mL of the dyes. A volume of 2.6 ml of the Fricke solution modified with photosensitizers were transferred to test tubes and irradiated. The irradiated solutions had their optical densities measured in a spectrophotometer. The samples were irradiated with LED (Light Emitting Diodes) in acrylic phantoms. The FATA samples irradiated with LED showed the sensitivity of the dosimeters to red, blue, green and yellow light. A calibration curve with correlation coefficient of 0.9884 for the red light was obtained; 0.9752 for blue light; 0.9644 for the green light and 0.9768 for the yellow light. The fact that a sensitivity of the dosimeters to the LED has been occurred indicates that the PDT could be realized with LED, with lower costs than with laser. This work suggested that FATA dosimeters can be used for quality control of PDT.